2013
DOI: 10.1155/2013/456156
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Weighted Imaging as a Useful Imaging Adjunct in Hemichorea Hyperglycaemia

Abstract: Hyperglycaemia with hemichorea (HGHC) is an unusual clinical entity that can be associated with corpus striatum hyperintensity on T1-weighted (T1W) magnetic resonance imaging (MRI) sequences. We report the utility of the susceptibility weighted image (SWI) sequence and the filtered phase SWI sequence in the imaging assessment of HGHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In this case, CT at the time of the second admission showed that the hyperdensity in the bilateral putamen had diminished compared with that at the time of the first admission; we speculate that the image change may have captured the process in which the hyperdensity that occurred at the time of the first admission was fading away. On MRI, T2-weighted, FLAIR, DWI, T2*, and SWI findings vary, although T1-weighted images typically show striatal hyperintensity [1,[8][9][10][11][12]. As in previous reports, striatal hyperintensity on T1-weighted MRI was the clearest diagnostic indicator of diabetic striatopathy in this case.…”
Section: Discussionsupporting
confidence: 54%
“…In this case, CT at the time of the second admission showed that the hyperdensity in the bilateral putamen had diminished compared with that at the time of the first admission; we speculate that the image change may have captured the process in which the hyperdensity that occurred at the time of the first admission was fading away. On MRI, T2-weighted, FLAIR, DWI, T2*, and SWI findings vary, although T1-weighted images typically show striatal hyperintensity [1,[8][9][10][11][12]. As in previous reports, striatal hyperintensity on T1-weighted MRI was the clearest diagnostic indicator of diabetic striatopathy in this case.…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, Dharsono et al, in a single case observed over 5 months, an improvement of hyperintensity on T1-MRI and a more extensive and increased SWI hypointensity within the affected corpus striatum, suggesting an ongoing process of deposition of paramagnetic material. Iron-deposition-related neurotoxicity could explain the progressive malacic change demonstrated on follow-up imaging [ 56 ] ( Table 1 ). Cherian et al suggested a paramagnetic mineral deposition in the affected putamen caused by swollen gemistocytes that express metallothionein and zinc secondary to ischemic insult [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other earlier studies used different imaging modalities in an attempt to elucidate the cellular function and perfusion status of the affected region. For instance, studies from DWI [ 54 ] and susceptibility-weighted MRI [ 55 ] suggested hyperviscosity with a cytotoxic edema and the deposition of paramagnetic material, respectively. Positron emission tomography studies demonstrated a marked decrease in glucose metabolism within the lesioned basal ganglia [ 20 , 56 ] and single-photon emission CT mostly revealed hypoperfusions in the corresponding region [ 57 ].…”
Section: Discussionmentioning
confidence: 99%